Proposed Approach to Develop Corporate Social Responsibility Activities at KSO Pertamina Depot Cikampek - Muhammad, Arisman; Rudito, Bambang (The Indonesian Journal of Business Administration, 2013)
Corporate race to do Corporate Social Responsibility (CSR) not only as marketing tools but also because Indonesian government has regulate it. In return, of corporate CSR, social legitimacy is established. CSR also can create corporate imaging in society; it will be good for company reputation in business world and can attract investors or other company who is willing to have partnerships. Pertamina Depot Cikampek is Pertamina depots manage by Pertamina Patra Niaga using Joint Operation (KSO) systems as a partner. Depot management has done some CSR programs, however community judges Depot management doing unsatisfying CSR program. Relation between Depot management with community and local administration are not go well. Research is done by doing observation, interviews and secondary data gathered from local administrations. From gathered data, it was found that communication between communities with the Depot is not running properly due to lack of a system to perform engagement. In addition, Depot management did not have planning for long term and sustain CSR program. Implementation begins from doing stakeholders analysis and mapping by doing stakeholders engagement. At the same time, CSR division should be establish and recruit its officers. After management can figure out community needs, they can start planning and preparation for CSR program. Lastly, implementation of program can be conducted. Ã‚Â Keywords: Pertamina Depot Cikampek, Corporate Social Responsibility, stakeholders engagement.